2020
DOI: 10.1007/s00520-020-05736-y
|View full text |Cite
|
Sign up to set email alerts
|

The provision of nutritional advice and care for cancer patients: a UK national survey of healthcare professionals

Abstract: Purpose People living with and beyond cancer often experience nutrition-related issues and should receive appropriate advice on nutrition that is consistent and evidence based. The aim of this study was to investigate current practice for the provision of nutritional care by healthcare professionals (HCPs) from a UK national survey produced by the National Institute for Health Research (NIHR) Cancer and Nutrition Collaboration. Methods An online survey sent to professional groups and networks included questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Specific content needs nominated by cancer survivors suggest an awareness of comorbidity risks, such as cardiovascular disease and osteoporosis (Berry et al, 2014;Leach et al, 2015 (Anderson et al, 2013;Baker et al, 2015;Murphy et al, 2020;van Veen et al, 2017;Williams et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific content needs nominated by cancer survivors suggest an awareness of comorbidity risks, such as cardiovascular disease and osteoporosis (Berry et al, 2014;Leach et al, 2015 (Anderson et al, 2013;Baker et al, 2015;Murphy et al, 2020;van Veen et al, 2017;Williams et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to the preference identified in this review for specific, individualised recommendations. An exploration of clinicians’ perspectives was beyond the scope of this review; however, in previous studies, cancer care clinicians have reported limited knowledge regarding dietary recommendations and inadequate training to provide health behaviour counselling (Anderson et al, 2013; Baker et al, 2015; Murphy et al, 2020; van Veen et al, 2017; Williams et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, healthcare professionals involved in detecting patients at risk for malnutrition should share baseline nutritional screening tools to improve their confidence in advising cancer patients [86]. A recent survey showed that though oncologists, nurses and nutritionists discuss specific alimentary troubles with cancer patients and may provide information, many of them lack an awareness of guidelines and confidence in providing nutritional advice [87]. Secondly, adapted tools or apps may facilitate the engagement of patients within the nutritional track [88]; In Italy, we developed in collaboration with AIOM, SINPE and FAVO (Federazione Italiana delle Associazioni di Volontariato in Oncologia) the app Nutrient to easily screen patients at higher risk for malnutrition which may benefit from an early referral to experienced nutritionists [89].…”
Section: Nutritional Care During Cancer Treatment: the Changing Role Of Oncologists Nutritionists And Nursesmentioning
confidence: 99%
“… 8 , 19 , 20 , 21 , 42 , 43 In particular, it had been found that oncology nurses were less aware of the guidelines and received less relevant nutritional training than physicians and dietitians. 21 , 44 The “Putting Evidence into Practice” resource widely used in oncology nursing does not include cachexia, but instead describes it as anorexia, and there are fewer evidence-based interventions than other symptom management techniques. 45 There are few nurse-led studies for cancer cachexia, and nurses rarely learn about cancer cachexia in pre-graduate education.…”
Section: Discussionmentioning
confidence: 99%